Physical-chemical, microbiological and ecotoxicological characterization of the pluvial waters of the uran Santos drainage system (São Paulo, Brazil) (Research, Society and Development, 2020)
The municipality of Santos, State of São Paulo, has as its characteristic drainage channels of rainwater that cuts across the city (channels 1 to 7). The general objective of this study was to analyze the quality of the urban rainwater of the drainage system of the municipality of Santos, during periods of high rainfall. Microbiological, physicochemical, chemical and ecotoxicological analyzes were performed. The collection procedures followed a research context of the rainwater trajectory sequentially captured at each point of analysis: rainwater, water in the gutter, exit of the gallery and water deposited in the channel. The results were evaluated based on the parameters established by resolutions CONAMA 274/00 and CONAMA 357/05. Compared to the specific localities in channel 3 (old and higher population density) and in channel 7 (new occupation area and with a lower population index), it was possible to determine the existence of domestic sewage, having a higher number of contaminated points In channel 3 and in channel 7 presented a point contamination in its gallery. The study demonstrated the presence of contaminants of anthropic influence, from the urban environment to the irregular connection of sanitary sewage at the points analyzed in this research. The presence of these contaminants in the urban drainage system of rainwater can have environmental consequences for the aquatic biota (present in the receiving body) and also for human health through contact with these waters.